An Effect Of Methanol Extract Sunkist Orange Peel (Citrus Sinensis (L.) Osbeck) On Blood Sugar And Cholesterol Levels Wistar Rats (Rattus Norvegicus) Induced By Aloxan - Yolanda Eliza Putri Lubis; Reghita Claudia Malau; Rahmi Arianti; Maya Sari Mutia (CV. Inara, 2023)
Insulin resistance is a condition with damage to target organs that generally respond to the activity of the hormone insulin. About 10% of the population in big cities in Indonesia suffer from insulin resistance. At the cellular level, insulin resistance can result from damage to the pre-receptor, receptor, or post-receptor. The most common cause of insulin resistance is post-receptor damage, namely disruption and damage to insulin signaling pathways. To find out that the methanol extract of Sunkist orange peel can reduce blood sugar levels in Wistar rats. This research uses the experimental laboratory method in vivo with the chosen research design form, namely True Experimental Pre Test and Post Test Control. The Kruskal Wallis test showed that the Sunkist Orange Peel Methanol Extract resulted in a significant decrease in blood sugar levels of Wistar rats with a p-value <0.05, and also the Anova test showed that the Sunkist Orange Peel Methanol Extract resulted in a decrease in blood sugar levels of Wistar rats, which is significant with p-value <0.05. All doses tested affect lowering blood sugar levels, namely, 300 mg/kg BW, 450 mg/kg BW, and 600 mg/kg BW.